2020
DOI: 10.1177/8755122520901739
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Assessment of Chemotherapy Adherence and Supportive Therapy Adherence on Occurrence and Minimization of Adverse Drug Reactions Among Cancer Patients: A Clinical-Based Observational Study

Abstract: Background: Cancer is a disease that is inevitably treated using chemotherapy, but the cytotoxic drugs used in the treatment have the potency to cause adverse drug reactions (ADRs). Thus, supportive therapy plays an essential role in managing the untoward effects of the cancer drugs in patients. This highlights the importance of medication adherence in managing the disease, mitigating and preventing the occurrence of chemotherapy-induced ADR without compromising the health status of the cancer population. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
2
1
Order By: Relevance
“…As a result, men were found to be less adherent than women. This finding is consistent with a study conducted in India 33 in which men had a nearly threefold increase in the risk of non-adherence when compared to women. This is due to the fact that men are burdened by outdoor activities that keep them busy and cause them to forget their medications.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, men were found to be less adherent than women. This finding is consistent with a study conducted in India 33 in which men had a nearly threefold increase in the risk of non-adherence when compared to women. This is due to the fact that men are burdened by outdoor activities that keep them busy and cause them to forget their medications.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with women, men had lower adherence. This nding is in line with a study performed in India (30). This might be because most of the time, females are more strict and may obey the direction of a health care worker's advice for medication adherence.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that the proportion of cancer patients in the Amhara region of Northeast Ethiopia who were receiving chemotherapy was 42.3% (95% CI, 37.6-46.7). The proportion of patients receiving chemotherapy in this study was greater than that in studies conducted in Nigeria (19.1%) (29) and India (21.1%) (30).…”
Section: Discussioncontrasting
confidence: 79%
“…Cancer is a global disease which is certainly managed and treated using cytotoxic drugs (CDs). 1 The CDs are toxic in nature. International Agency for Research on Cancer (IARC) have classified some of the anti-cancer agents as human carcinogens.…”
Section: Introductionmentioning
confidence: 99%